Peningkatan Kecerdasan Intrapersonal Guru Pendidikan Anak Usia Dini melalui Penyuluhan Program Parenting - Alam, Syah Khalif; Wulansuci, Ghina; Rohmalina, Rohmalina (Universitas Pendidikan Ganesha, 2019)
Professional competence and teacher pedagogy are the main elements that are always considered in improving the quality of teachers and education. In carrying out their duties and roles as instructors as well as educators, teachers need to have the ability to manage emotions and understand themselves, namely intrapersonal intelligence. Early childhood education teachers in Padalarang Regency feel less able to manage their intrapersonal intelligence, this is due to the lack of communication and collaboration between parents and schools. Resulting in teachers feeling optimal about providing learning to their students. Teachers in Padalarang Regency are of the opinion that the ability to manage intrapersonal intelligence is important to improve, in order to be able to renew or make changes for themselves and for the world of education. The ability to manage intrapersonal intelligence sometimes can not with one's own awareness, it needs input from others in order to manage intrapersonal intelligence properly. the parenting counseling program for kindergarten teachers in Padalarang regency was carried out as an effort to increase teacher intrapersonal intelligence. The results of the activities that have been achieved are the Padalarang Regency Kindergarten teacher is understanding the importance of parent involvement in the school, as a bridge to increase teacher intrapersonal intelligence.